2012
DOI: 10.5021/ad.2012.24.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 1,064 nm Q-switched Nd:YAG Laser Treatment for Removing Melanocytic Nevi

Abstract: BackgroundUntil recently, the removal of melanocytic nevi has been performed with a CO2 laser or Er:YAG laser. These lasers have been useful for removing affected spots. However, enlargement of spots or some sequelae, including depressed or hypertrophic scars, could develop as unwanted results. The Q-switched Nd:YAG laser has been used to remove deep-seated melanocytes, such as Ota nevus or tattoos. However, there have been no previous experiments performed to test the efficacy and safety of this laser treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 12 publications
3
26
0
1
Order By: Relevance
“…Furthermore, medical complication rates were high, with reported scarring in up to 25%, and wound infection in up to 18% . Several small studies have reported dramatic improvements and high levels of patient satisfaction after superficial removal techniques; however, improvements in colour were judged subjectively and immediately postintervention . Furthermore, several reports and studies still advocate early aggressive intervention in CMN with superficial removal techniques with outcomes reported by direct comparison of results to early postnatal pictures .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, medical complication rates were high, with reported scarring in up to 25%, and wound infection in up to 18% . Several small studies have reported dramatic improvements and high levels of patient satisfaction after superficial removal techniques; however, improvements in colour were judged subjectively and immediately postintervention . Furthermore, several reports and studies still advocate early aggressive intervention in CMN with superficial removal techniques with outcomes reported by direct comparison of results to early postnatal pictures .…”
Section: Discussionmentioning
confidence: 99%
“…Good results for small common AMNs have also been obtained with the short-pulse Erbium: YAG laser,[14] and the QS Nd: YAG laser in Asian skin [Table 3]. [1516] Future head-to-head studies comparing these lasers, the μsAL laser, the msAL laser and the carbon dioxide laser will be useful to identify the preferred laser for the removal of facial AMNs in Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests water as the primary chromophore inducing a dermal inside-out heating. 16 Moreover, the photoacoustic effect triggered by the pocket cell (in the nanosecond domain) of this Q-switched technology, can create intradermal cavitation 17 in and around the targeted structure. Such mega-pulse of light energy may then, in turn, destroy/implode even bone structures (osteoma cutis) in the dermis followed by a wound healing response without epidermal damage, reducing the risk of pigmentary changes in darker phototype individuals.…”
Section: Discussionmentioning
confidence: 99%